A three-stage sequential surgical approach to a more efficient management of clinical stage 4 diabetic foot ulcers - Zhang, Fang; Guo, Yu; Zhang, Wenduo; Dal Prà, Ilaria; Chen, Wei; Mo, Xiaojin; Song, Hehua; Chiarini, Anna; Yang, Jinpiao; Nie, Kaiyu; Wei, Zairong; Chang, Shusen (Frontiers in Surgery, 2025)
BackgroundIt has been a great challenge to treat clinical stage 4 Diabetic foot ulcers (DFUs) due to high rates of major amputations and prolonged healing time. This study aimed to assess the effectiveness of a three-stage sequential surgical approach, which based on the Integrated Surgery Wound Treatment (ISWT) mode, to manage clinical stage 4 DFUs and compare the benefit of incorporating tibial cortex transverse transport (TTT) surgery at stage 3 treatment.MethodsTwenty-three patients with clinical stage 4 DFUs aged 45–75 years treated between January 2022 and February 2023 were retrospectively analyzed. Eleven patients (Group A) received wound debridement, antibiotic-loaded bone cement (ALBC) at stage 1 treatment, percutaneous transluminal angioplasty (PTA), wound debridement, and ALBC at stage 2 treatment, and skin grafting with TTT at stage 3 treatment, while twelve patients (Group B) received the same treatment without TTT. Assessed clinical outcomes included length of hospital stay, ulcer healing duration, ulcer recurrence rate, reintervention (re)-PTA rate, amputation rate, mortality rate, visual analog scale (VAS) scores, ankle-brachial index (ABI), and two-point discrimination (2-PD) ability. The computed tomographic angiography (CTA) was used to evaluate vascular hyperplasia.ResultsGroup A showed no occurrences of re-PTA (P = 0.037) and similar ulcer healing times (P = 0.975) compared to Group B. Ulcer outcome, amputation, and mortality rate were also alike in the two groups (P > 0.05). One year after surgery, Group A demonstrated improvement in VAS scores, ABI, and 2-PD, while Group B showed no significant changes. Additionally, Group A exhibited enhanced lower limb artery characteristics compared to Group B.ConclusionThe sequential three-stage approach based on the ISWT mode effectively manages clinical stage 4 DFUs. Incorporating TTT surgery at stage 3 extends the benefits of PTA surgery.